2004
DOI: 10.1128/aac.48.5.1811-1822.2004
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Respiratory Syncytial Virus (RSV) Neutralizing Antibody Decreases Lung Inflammation, Airway Obstruction, and Airway Hyperresponsiveness in a Murine RSV Model

Abstract: Numerous studies have described a strong association between respiratory syncytial virus (RSV) infection in infancy and the development of recurrent wheezing and airway hyperresponsiveness. We evaluated the effect of an anti-RSV neutralizing monoclonal antibody (palivizumab) on different aspects of RSV disease by using a murine model. BALB/c mice were intranasally inoculated with RSV A2. Palivizumab or an isotype-matched control antibody was administered once at 24 h before inoculation, 1 h after inoculation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 59 publications
6
83
0
1
Order By: Relevance
“…Many similarities can be found between hMPV and hRSV replication in BALB/c mice. Following an intranasal challenge, hRSV lung titers peak on day 4 postinfection with no viruses usually recovered beyond day 7 (22,29). On the other hand, hMPV titers peaked on day 5 in our model and viruses could still be recovered on day 12 but not by day 21 (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Many similarities can be found between hMPV and hRSV replication in BALB/c mice. Following an intranasal challenge, hRSV lung titers peak on day 4 postinfection with no viruses usually recovered beyond day 7 (22,29). On the other hand, hMPV titers peaked on day 5 in our model and viruses could still be recovered on day 12 but not by day 21 (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…In our initial report, we described a difference in weight loss between AKR/J and C57BL/6J mice, with AKR/J mice demonstrating higher titers and greater weight loss (56). One of the most convincing demonstrations of the association between RSV titers and clinical indicators of disease in mice was described by Ramilo and associates (41). Their study demonstrated that reduced RSV replication (lower titer) was associated Representative transcripts increased more in C57BL/6J than in AKR/J mouse lungs during RSV infection and indicative of T-cell and nucleosome involvement.…”
Section: Vol 84 2010 Genetic Analyses Of Rsv Susceptibility 2263mentioning
confidence: 90%
“…Prophylactic Effects of Anti-RSV-G and Anti-RSV-F mAbs in the Response to Primary RSV Infection Previous studies in a mouse model showed a prophylactic effect of palivizumab on AHR and airway inflammation (19). Mice were infected on Day 0 at 6 weeks of age; anti-RSV-G (3G12) or anti-RSV-F was administered intraperitoneally at 15 mg/kg on Day 21.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in efficacy were more obvious when treatment was initiated after infection. Anti-RSV-F failed to demonstrate therapeutic effects in RSV disease in animals (19) or humans (5), even though the viral titer was lower after treatment. These results suggested that once infection was established, host responses continued to contribute to disease pathogenesis.…”
Section: Cx3cr1mentioning
confidence: 99%
See 1 more Smart Citation